Pengaruh Direct Method Berbantuan Aplikasi FonBi terhadap Keterampilan Menyaji Teks Laporan Pengamatan Siswa Kelas VII SMPN 2 Pariaman - Nurul Suryani; Nursaid Nursaid; Claudhea Detrial Enjelina; Annisa Nurul Rahma; Vebby Novedra Utami (DIDAKTIKA, 2024)
This study aims to determine the level of students' ability to present the text of observation reports before and after using the Direct Method model assisted by the FonBi application in grade VIII SMPN 2 Pariaman, and to evaluate the significant effect of using the Direct Method model assisted by the FonBi application on students' skills in presenting the text of observation reports in grade VIII SMPN 2 Pariaman. The type of research conducted in this study is quantitative, quasi-experimental research. The research design used in this study was One Group Pretest-Posttest Design. Research sampling is carried out using judgment sampling techniques or authority techniques for sample selection. This research data is the score of the test results of the skill of presenting the text of the observation report before the Direct Method model assisted by the FonBi application and after the Direct Method model assisted by the FonBi application was applied. The instrument used in this study was a test. The form of test used in this study is a performance test. In this study, there are four indicators of skills in presenting the text of the observation report, namely (1) pronunciation, (2) pressure, (3) pause and intonation, (4) communication.